PENGARUH LATIHAN LARI DENGAN TAHANAN TERHADAP KECEPATAN LARI SPRINT 100 METER SISWA ANGGOTA EKSTRAKURIKULER SEPAK BOLA SMP NEGERI 4 SIAK HULU - Mukhlis '; Slamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of thisresearch is based on the observation of thestudent extracurricular football SMP Negeri 4 Siak Hulu. Problems that researchers getare: speed sprint football student extracurricular member SMP Negeri 4 Siak Hulu isnot maximized. The basic technique sprint football student extracurricular memberSMP Negeri 4 Siak Hulu has not been well understood. students never get specialtraining sprint by teacher coaches. The purpose of this study was to determine the effectof exercise training effect run by pulling a load to the speed of 100 meter sprint footballextracurricular student members SMP Negeri 4 Siak Hulu. This research is a kind ofexperiment.Based on the test results of normality, the data are normally distributed. Based onthe calculation t test. T-test calculation results obtained t value at 6:22. the value is thencompared with the value t table. T table value at n = 15 or df = 14, at the level of 1%error is = 2.98 and 5% was 2.14. the results of the comparison atara t value with thevalue t table as follows: T Table (1%) <T arithmetic> T table (5%) or 2.98 <6.22>2.14 Based on the above comparison it is known that the hypothesis which says there isa practice run with an interesting effect the burden of the 100 meter sprint speed studentextracurricular member football SMP Negeri 4 Siak Hulu acceptable.Keywords : 100 meter sprint, running training with pulling loads